1998
DOI: 10.1590/s0102-311x1998000700014
|View full text |Cite
|
Sign up to set email alerts
|

Mammography and Pap test screening among low-income foreign-born Hispanic women in the USA

Abstract: Little is known about the factors influencing screening among low-income Hi s p a n i c women part i c u l a rly among recent immigra n t s . A sample of 148 low -i n c o m e , l ow -l i t e ra t e , f o reign-born Hispanic women residing in the Washington n i n g g u i d e l i n e s . Women in this study had more misconceptions about cancer than Hispanics in other s t u d i e s . Mu l t i variate logistic models for correlates of Pap test and mammography screening behavior indicate that factors such as fear o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
2

Year Published

2000
2000
2009
2009

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 40 publications
(6 reference statements)
1
20
0
2
Order By: Relevance
“…Other studies have found lack of English language proficiency to be an important barrier to screening. 22,41,42 Interestingly, only levels of language acculturation were significant predictors for BSE and CBE compliance. This could be because limited proficiency in English is associated with underlying socioeconomic factors that decrease the use of healthcare services.…”
Section: Breast Cancer Screening Among Immigrant Iranian Women 495mentioning
confidence: 97%
“…Other studies have found lack of English language proficiency to be an important barrier to screening. 22,41,42 Interestingly, only levels of language acculturation were significant predictors for BSE and CBE compliance. This could be because limited proficiency in English is associated with underlying socioeconomic factors that decrease the use of healthcare services.…”
Section: Breast Cancer Screening Among Immigrant Iranian Women 495mentioning
confidence: 97%
“…[7][8][9][10][11] Studies carried out in Australia found screening rates to be lowest among women born in Vietnam, 12 and also in women living in areas with the highest proportion of non-English speaking background migrants and the lowest socio-economic status. 13 In many studies, migration has been suggested as a social factor that puts women at-risk of falling into lower socio-economic status associated with poor access to screening.…”
Section: Taylor Et Al Articlementioning
confidence: 99%
“…[1][2][3] However, mammography screening rates among Latinas are declining. [4][5][6][7][8][9][10] This trend may be due to a number of factors including increases in rates of being uninsured, access to health-care, [11][12][13][14][15][16] not enough Spanish-speaking providers to meet demands, perceptions of provider bias, and/or a lack of sufficient culturally competent services. 12,15,[17][18][19][20][21][22] Though approximately 86% of adult Latinos report having contact with a primary care physician, 23,24 Latinas report lower satisfaction with their care than do non-Latina whites.…”
Section: Introductionmentioning
confidence: 99%